From Inter-modal Transport Services to Integrated Common Objectives - Fleischer, T. (Acta Technica Jaurinensis, 2011)
The article starts from the paradigm of modernity and its connection to the technological basis with special regards to the technological determinations in the development of the transport modes. As a contrast to the approach, the next parts deal with the excess of the barriers at a paradigm level, introducing the connection of the problems with the different integrations. Integrations mean here both the common planning of the city with the conurbation area (territorial integration), the common handling of different transport modes (inter-modality, co-modality) and the transfer between technological platforms (interoperability). As a representation of the problems, the article presents and interprets the recent development of the plans for the public transport backbone network of Budapest and its environ. A further case for the integrated approach is the new integrated transport strategy for Hungary: where just the preparation phase begins in this year.